Conditioning to the core - Brittenham, G.; Taylor, D. (Human Kinetics, 2014)
Condition the core; unleash the potential. Serious athletes train for results—results that make them winners on the field, pitch, course, or court. And the key to getting those results, to improving performance in any sport and at any level, is no secret. A strong, well-conditioned core is the lynchpin to athletic success.